Gender Characteristics of Advertising Texts (for the Example of French and Uzbek Languages) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
One of the most remarkable scientific innovations of recent years is the emergence of a new approach to language learning, the issue of gender. In addition to philology, the concept of gender can be seen in the fields of philosophy, history, sociology, anthropology, economics, psychology and a number of other sciences. In this article, we will discuss the significant features of gender in French printed advertising texts, the type of advertising product, the size and structure of the advertising text - word, phrase, sentence, slogan, morphological, lexical, word formation and syntactic features of the text and the influence of the gender factor in it. the secret will be revealed.